Modellierung und Derivation in der Phraseologie. Der Fall der hyperbolischen Verbalphraseme im Deutschen - Komenda-Earle, Barbara (2023)
The paper deals with selected hyperbolic verbal phrasemes of German and their formation mechanisms. Hyperbolic metaphor and hyperbole are present as semantic-rhetorical foundations of the formation of the studied phrasemes and are not only based on semantic-syntactic combinations within the phraseological components, but also on corresponding cognitive structures (metaphor models and metonymies). Both types of operations are explained in the article. The formation mechanisms of hyperbolic verbal phrasemes enter into larger areas of study of phraseology: modeling of phraseological systems and phraseological derivation. Hyperbolic verbal phrasemes as typically idiosyncratic units prove to be modelable, i.e. describable in series within syntactic-semantic schemata. They are also subject to lively derivational processes, i.e. they form the basis for the emergence of new phrasemes. Modeling and derivation are thus important factors in the formation of hyperbolic verbal phrases and are also explained in the article.
Keywords: hyperbolic phrasemes; somatisms; modeling in phraseology; phraseological derivation; metaphor modells; metonymy